Faktor-Faktor yang Mempengaruhi Keputusan Petani dalam Pemilihan Varietas Benih Padi Unggul di Kecamatan Gedong Tataan Kabupaten Pesawaran: Factors Influencing Farmers Decisions in Selection of Superior Rice Seed Varieties in Gedong Tataan District, Pesawaran Regency - Alya Desilva; Citra Ramadhan Permata Okna; Farra Agustina Sila Sila; Irwan Effendi; Indah listiana (Research and Social Study Institute (RESSI), 2023)
Farmers' decision-making also influences the development of superior varieties. This is related to the properties possessed by superior varieties. This study aims to determine the characteristics of rice farmers in selecting varieties of rice seeds and the factors that influence the farmers' decision-making process. This research was conducted in Gedong Tataan District, Karang Anyar Village, Pesawaran Regency from October to December 2022. This research was conducted using a survey method, the respondents in this study amounted to 25 farmers who were taken purposively (purposive). The hypothesis put forward in this study is that there is a significant relationship between farmer characteristics including age, education level, experience, dependents, land area, seed quality and seed resistance to pests and diseases. Descriptive analysis of data and hypothesis testing using the Rank's Spearman correlation method. The results showed that the factors that influence farmers' decisions in choosing rice varieties are mostly in the low classification. The results of the Rank's Spearman correlation test showed that farmers' decisions in choosing rice seed varieties had no significant relationship with age, education level, experience, dependents and land area, while seed quality and seed resistance to pests and diseases had a significant relationship with farmers' decisions in choosing rice seed varieties.